PENGARUH TEKANAN ANGGARAN, WAKTU, RISIKO AUDIT, LOCUS OF CONTROL DAN KOMITMEN PROFESIONAL TERHADAP PERILAKU PENURUNAN KUALITAS AUDIT (REDUCED AUDIT QUALITY BEHAVIOR (STUDI EMPIRIS BPK RI PERWAKILAN PROVINSI RIAU) - Diana, Haugesti; Azlina, Nur (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
This study aimed to examine the influence of time budget pressure, locus of control,audit risk, locus of control and dimension of professional commitment to reducedaudit quality behavior.Respondents of the research is auditor who works in BPK RIRepresentative of Riau Province. Research samples are 53 responden Theresearch uses multiple regression analysis. Prior to the tests, conducted prior testdata quality (reliability and validity), test data normality and classical assumptiontest. The results of this research indicate that 1) Time budget pressure effect onreduced audit quality behavior, 2) audit risk effect on reduced audit quality behavior,3) locus of control no effect on reduced audit quality behavior, and 5) dimensions ofprofessional commitment that is professional commitment affective, professionalcommitment continuance professional commitment normative effect on reducedaudit quality behavior.Key words: Reduced audit quality behavior, Time budget pressure, audit risk, Locusof Control, professional commitment affective, professional commitmentcontinuance, professional commitment normative.